Infection of the brown alga Ectocarpus siliculosus by the oomycete Eurychasma dicksonii induces oxidative stress and halogen metabolism. (23rd April 2015) - Strittmatter, Martina; Grenville‐Briggs, Laura J.; Breithut, Lisa; Van West, Pieter; Gachon, Claire M. M.; Küpper, Frithjof C.
Abstract: Pathogens are increasingly being recognized as key evolutionary and ecological drivers in marine ecosystems. Defence mechanisms of seaweeds, however, have mostly been investigated by mimicking infection using elicitors. We have established an experimental pathosystem between the genome brown model seaweed E ctocarpus siliculosus and the oomycete E urychasma dicksonii as a powerful new tool to investigate algal responses to infection. Using proteomics, we identified 21 algal proteins differentially accumulated in response to E u. dicksonii infection. These include classical algal stress response proteins such as a manganese superoxide dismutase, heat shock proteins 70 and a vanadium bromoperoxidase. Transcriptional profiling by qPCR confirmed the induction of the latter during infection. The accumulation of hydrogen peroxide was observed at different infection stages via histochemical staining. Inhibitor studies confirmed that the main source of hydrogen peroxide is superoxide converted by superoxide dismutase. Our data give an unprecedented global overview of brown algal responses to pathogen infection, and highlight the importance of oxidative stress and halogen metabolism in these interactions. This suggests overlapping defence pathways with herbivores and abiotic stresses. We also identify previously unreported actors, in particular a Rad23 and a plastid–lipid‐associated protein, providing novel insights into the infection and defence processes in brown algae. Abstract : Macroalgal response to pathogen infection has mostly been studied by mimicking infection using elicitors. We have established a pathosystem between the genome model seaweed E ctocarpus siliculosus and the oomycete E urychasma dicksonii as a powerful new tool to investigate algal responses to infection via a combined approach of proteomics, qPCR and histochemial staining. Our data give an unprecedented global overview of brown algal response to pathogen infection, and highlight the importance of oxidative stress and halogen metabolism in these interactions.